Investigating The Effectiveness Of Digital Storytelling In Developing Algerian Learners’ Emotional Intelligence: A Case Study Of Third Year Lmd Students Of English At Abdelhamid Ibn Badis University - Imene Zoulikha Kassous; Hanane Sarnou (The Journal of Studies in Language, Culture and Society)
Digital storytelling (henceforward DST) refers to the idea of mixing the traditional art of storytelling with a variety of technological and digital devices. It is one of the most effective teaching and learning techniques used by teachers to promote social-emotional learning atmosphere. The proponents of DST believe that this technique can enhance students’ engagement, achievement and motivation. In this respect, this instructional innovation has revolutionized the traditional educational practices with its crucial role in developing learners’ competencies, especially emotional intelligence (henceforward EI). This research paper investigates the effectiveness of using digital storytelling, in the department of English language at Abdelhamid Ibn Badis University in Mostaganem, Algeria. It also examines the effects of this innovative technique on developing English as foreign language (henceforward EFL) learners’ emotional intelligence. We employed a mixed-method design to cover the principal elements and queries of the research. We conducted an experiment that lasted for four weeks, classroom observation and an emotional intelligence test for learners. The target population consisted of 44 third year bachelor students. They belonged to group one and group five at the University of Mostaganem. They were randomly selected to test the effectiveness of DST in developing their emotional intelligence. The results revealed a significant development the emotional intelligence of learners due to DST project.